2001
DOI: 10.2337/diacare.24.9.1579
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Arg/Arg, but not Trp/Arg, of the Trp64Arg Polymorphism of the β3-Adrenergic Receptor Is Associated With Type 2 Diabetes and Obesity in a Large Japanese Sample

Abstract: OBJECTIVE -Despite a large number of studies, no association of the Trp64Arg polymorphism of the ␤ 3 -adrenergic receptor gene with obesity and type 2 diabetes has yet to be clearly elucidated. We examined the associations in a large population-based sample.RESEARCH DESIGN AND METHODS -A total of 1,685 subjects (935 women and 750 men, aged 58.7 Ϯ 12.4 years) from a cohort population (n ϭ 3,706) of the Funagata Diabetes Study were divided into three groups according to genotypes: Trp/Trp (n ϭ 1,155), Trp/Arg (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 32 publications
(19 reference statements)
4
39
1
Order By: Relevance
“…24 In previous epidemiologic studies, the association between the ADRB3 variant and obesity-related phenotypes has been investigated among individuals from several racial/ ethnic groups and nationalities, including Caucasians, 13 Japanese, 12,25,26 Pima Indians, 24 Mexican Americans, 14 African Americans 27,28 and Jamaicans. 29 Previous studies of white or Japanese populations found the variant allele of the ADRB3 receptor to be associated with elevated measures of obesity, 13 whereas two previous studies of African Americans reported associations with the wild-type receptor.…”
Section: Adrb3 and Obesity R Mckean-cowdin Et Almentioning
confidence: 99%
See 3 more Smart Citations
“…24 In previous epidemiologic studies, the association between the ADRB3 variant and obesity-related phenotypes has been investigated among individuals from several racial/ ethnic groups and nationalities, including Caucasians, 13 Japanese, 12,25,26 Pima Indians, 24 Mexican Americans, 14 African Americans 27,28 and Jamaicans. 29 Previous studies of white or Japanese populations found the variant allele of the ADRB3 receptor to be associated with elevated measures of obesity, 13 whereas two previous studies of African Americans reported associations with the wild-type receptor.…”
Section: Adrb3 and Obesity R Mckean-cowdin Et Almentioning
confidence: 99%
“…11 The ADRB3 gene is highly conserved between humans and rodents and its functional impairment may lead to obesity by altering metabolic processes of fat tissue. 11,12 The receptor is expressed in visceral and subcutaneous fat tissue, but is more abundant and active in visceral tissue. 11 A missense change at codon 64 of this gene (Trp64Arg) has been identified and has been associated with measures of obesity, [12][13][14] weight gain, 15 insulin resistance 13 and type II diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two polymorphisms in the β2-adrenergic receptors (arginine/glycine substitution, Arg16Gly; and glutamine/ glutamate substitution, Gln27Glu) of the β2-adrenoceptor gene were studied (6,7). One polymorphism (tryptophan/ arginine substitution, Trp64Arg) of the β3-adrenoceptor gene was also studied (10).…”
Section: Genotypingmentioning
confidence: 99%